Rancang Bangun Quadrotor Dengan Kendali Robust Pid Untuk Pemetaan Sawah Pra Panen - Rendra Dwi Firmansyah; Budi Sumanto; Rella Mareta (Jurnal Nasional Teknologi Terapan (JNTT), 2018)
Field mapping is important to know the potential of agricultural productivity in a region.Furthermore, field mapping can also be used to predict crops in a region. The mapping can be donethrough aerial photographs. Aerial photographs can be performed using manned aerial vehicle aswell as unmanned aerial vehicle. Currently, many aerial photographs are taken using unmannedaerial vehicle because the cost is much more affordable than using a manned aerial vehicle. One typeof unmanned aircraft used for aerial photographs is quadcopter. However taking aerial photographsusing a quadcopter often produces blurry images due to its instability. Instability of the quadcopter iscaused by several factors including sensor readings such as IMU, GPS, compass, and barometer,disturbance factors such as angina, and control systems that are less robust to quadcopter characters.To get a stable quadcopter, a control system that matches the quadcopter character and has aresistance to interference is needed. One of the control systems that can be applied to the quadcopteris the Robust PID control system. Reliability of the control system can be seen using ITAE (IntegralTime Absolute Error). The smaller the value of ITAE the better the control system. Some tuningmethods are done to get the Robust PID control system. The method used in this research is ZieglerNicols, fine tuned PID controller, and ITAE tuning method. The result of PID constant tuning is thenimplemented to quadcopter. In this study the response data was obtained by using IMU sensor. Theresult shows that of the three tuning methods implemented in the quadcopter, the Fine tuning methodgives better results than the others.